Heavy-duty sewing : making backpacks and other stuff - Sandqvist, Anton (Frances Lincoln, 2018)
From the founder of iconic outdoors brand Sandqvist, this cool craft book is all about using needle and thread, a sewing machine and stiff materials to make your own practical, hardwearing functional objects. From hiking rucksacks to knife holders, vanity bags to aprons, there are projects for the experienced home sewer who is looking to try something new, for people who find the idea of sewing fun but may not have come up with a suitable project and for those who have never even used a sewing machine before. Explaining the basics of making textile products and which materials to use, as well as the equipment and work techniques, this book teaches you all about leather and how to repair your own belongings. You then have the chance to put these techniques into practice by turning your hand at ten cool projects for countryside, town and travel. There is no difficult stitching here; you simply need some patience and attention to detail. Amazingly good fun and rewarding, welcome to heavy-duty sewing!